Comparison of the cardioprotective and renoprotective effects of the L/N‐type calcium channel blocker, cilnidipine, in adriamycin‐treated spontaneously‐hypertensive rats. (April 2015) - Aritomi, Shizuka; Harada, Eri; Sugino, Kazumi; Nishimura, Mai; Nakamura, Tarou; Takahara, Akira
Summary: Cilnidipine is an L/N‐type calcium channel blocker (CCB). The effects of cilnidipine on N‐type channels give it unique organ‐protective properties via the suppression of hyperactivity in the sympathetic nervous system (SNS) and renin‐angiotensin‐aldosterone system (RAAS). In the present study, we compared the effects of cilnidipine and amlodipine (an L‐type CCB) on cardiac and renal functions in spontaneously‐hypertensive rats injected with adriamycin (ADR). After the weekly administration of ADR for 3 weeks, spontaneously‐hypertensive rats were orally administered cilnidipine (20 mg/kg per day), amlodipine (3 mg/kg per day), or vehicle once daily for 4 weeks. A control group received saline rather than ADR, followed by vehicle for 4 weeks. Cilnidipine and amlodipine produced similar reductions in blood pressure after 4 weeks. Cilnidipine ameliorated ADR‐induced heart and kidney damage, whereas amlodipine slightly improved cardiac echocardiographic parameters, but did not protect against ADR‐induced renal damage. Cilnidipine (but not amlodipine) suppressed the reflex SNS and RAAS hyperactivity caused by their antihypertensive effects. Furthermore, cilnidipine and amlodipine treatment decreased the urinary levels of adrenocortical hormones. The protective effects of cilnidipine against ADR‐induced renal and cardiac dysfunction might be associated with its blockade of N‐type calcium channels, in addition to its pleiotropic actions, which include the inhibition of the RAAS.